In Search of the Main Cause of the Spread of the Gold Standard Before World War I: an Attempt at Classification and Preliminary Assessment of Positions - Luszniewicz, Jacek (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The aim of the article is to outline the history of the spread of gold standard before 1914, to identify and conceptualise representative positions as regards causes of this process, and finally, to provide preliminary assessment of the presented arguments. Gold monometallism was born in Great Britain in the late 18th century (de facto) and shortly a!er the Napoleonic Wars (de iure). First followers emerged in the thh and sixth decade of the 19th century, but most numerous transfers to the gold standard were to be witnessed in the 70s, 80s and 90s. On the verge of World War I, the gold standard functioned, formally or actually, in over 80 territory units (states, semi-colonies, colonies) with approximately 45 different currencies. Alternative monetary systems, among others bimetallism and the silver standard, found themselves on the margin. Four groups of decision-motivations, determining the gold standard victory, are discussed in the source literature. The author classifies them as imitation-status, political-social, technological-institutional and functional-situational motivations, and analyses in further sections of the article, respectively. The conclusion is that all distinguished groups of motivations are prone to falsifying criticism. Hence, instead of searching decisive ’flywheels’ responsible for the gold standard domination in the pre-first-war world, historians and economists should explore in their studies more than ever specific and changing decision-motivations of individual countries.(original abstract)